Examining Teaching Practises in Design and Craft Education in Iceland - Thorsteinsson, Gisli; Olafsson, Brynjar (The Design and Technology Association, 2017)
This article reports a survey which aimed to examine the present situation in Design and Craft Education (D&C) in Iceland in terms of teachers’ general standing and their teaching inside the Icelandic elementary schools. A questionnaire was sent to 170 D&C teachers in Icelandic elementary schools. The questionnaire was completed by 101 teachers, and the response rate was 59.4%. The main research questions were: 1. What are the most common methods for teaching D&C? 2. How do D&C teachers utilise the Icelandic National Curriculum? 3. How could the teaching better meet students’ individual needs? Data were collected using an online questionnaire that was distributed to D&C teachers in all elementary schools in Iceland. Findings showed that D&C teachers base their teaching mainly on direct instruction, but also use verbal explanation, practical demonstration and discussion with students during their work. The teachers were quite satisfied with their methods of teaching and were not willing to make dramatic changes. Nevertheless, they were interested in improving outdoor education, field trips and the use of information and communication technology (ICT) in their classrooms. Most of the teachers used the national curriculum for planning their teaching, but generally only at the start of the school year. The research indicates the importance of improving the teachers’ practices in order to strengthen the subject’s status inside the Icelandic school system. This could be done via in-service teachers’ courses and seminars with teachers discussing the outcomes of the research.